Perbedaan Partisipasi Anggaran Ditinjau dari Jenis Jabatan, Tingkat Pendidikan, Jenis Kelamin dan Pengalaman Kerja (Studi Empirik pada Perguruan Tinggi Swasta di Daerah Istimewa Yogyakarta) - Cornelio Purwantini; Ignatius Bondan Suratno (Universitas Muhammadiyah Yogyakarta, Indonesia, 2007)
The purpose of this research was to know difference in the budget participation that’s evaluated from education levels, gender, occupations, and job experiences. The number of research sample is 198 people coming from 45 Private Higher Education Institution in Yogyakarta. The research subject is heads from of unit who are enganged in the budget partisipation, such as heads of study program, heads of department, vice dean, dean, heads of bureau and the like in Private Higher Education Institution. The data analysis was conducted using independent sample t test. The statistical test result with 0.05 of the significance level indicated that there was no difference in the budget participation that was evaluated from education levels, gender, occupation, and job experiences.